Extracellular stiffness as a determinant of cardiac dysfunction in duchenne muscular distrophy: a study on human iPSC derived cardiomyocytes. (10th June 2022) - Giammarino, L; Santini, L; Palandri, C; Musumeci, M; Langione, M; Pioner, JM; Ferrantini, C; Coppini, R; Cerbai, E; Poggesi, C
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Fondazione Intesa San Paolo Introduction: Duchenne muscular dystrophy (DMD) is a genetic disorder characterized by progressive degeneration of striated muscles; in addition to skeletal muscle impairment, DMD is also characterized by progressive myocardial disfunction. The low translational value of animal models and the low availability of human samples make DMD hard to investigate; induced pluripotent stem cells (iPSCs) represent a novel tool to model this disease, preserving the genetic heritage of the patient, including the pathogenic mutation causing dystrophy. Aim: Our aim is to characterize cardiomyocytes differentiated from iPSCs (iPSC-CMs) derived from healthy donors (CTRL) and DMD patients, to identify the pathophysiological mechanisms of DMD-related cardiomyopathy. Materials and Methods: Cardiomyocytes are differentiated from IPSCs obtained by reprogramming isolated mononucleated blood cells from healthy donors and DMD patients. IPSC-CMs are cultured until day 60, 75 or 90 post-differentiation after plating on nanostructured substrates with two different stiffness levels: PEG-substrates, with lower rigidity, mimicking healthy extracellular tissue, and DEG-substrates, with greater rigidity, that mimic the presence of myocardial fibrosis. Through imaging techniques, we evaluated calcium handling and action potentials (AP) on DMD and CTRL iPSC-CMs by using specific fluorescent dyes for Ca2+ (CAL630) and membrane voltage (Fluovolt). Cells were stimulated at different pacing rates. Results: The calcium transient amplitude of CTRL-iPSC-CMs became larger during maturation. This adaptation did not occur in DMD lines, showing a deficit calcium release due to poor maturation of the sarcoplasmic reticulum (SR). AP duration was shorter in the DMD line at d75 but at d90 we observed no differences when compared with the CTRL line. CTRL iPSC-CMs showed a marked ability to adapt to different substrate stiffnesses. Indeed, the calcium transient amplitude was larger and its kinetics faster when cells were grown on the rigid DEG substrates rather than on PEG plates. In the DMD line, however, no differences were observed between the substrates. Conclusions: Our results highlight a scarce ability of DMD iPSC-CM to adapt to different substrate stiffness, resulting in mechanical and electrical impairment, especially in the presence of stiffer substrates. This might explain why cardiac impairment is usually absent in the early stages of DMD, when cardiac structural changes are still absent. However, the electrophysiological and mechanical impairment of DMD hearts may precipitate rapidly when extracellular stiffness starts to increase due to development of cardiac fibrosis.